Quantification of the demands of cricket bowling and the relationship to injury risk: a systematic review - Matthew Constable; Daniel Wundersitz; Rodrigo Bini; Michael Kingsley (BMC, 2021)
Abstract Background Bowling in cricket is a complex sporting movement which, despite being well characterised, still produces a significant number of injuries each year. Fast bowlers are more likely to be injured than any other playing role. Frequency, duration, intensity and volume of bowling, which have been generalised as measurements of workload, are thought to be risk factors for injuries. Injury rates of fast bowlers have not reduced in recent years despite the implementation of various workload monitoring practices. Objective To identify the variables used to quantify frequency, intensity, time and volume of bowling; and evaluate relationships between these variables and injury risk. Methods Six online databases were systematically searched for studies on fast bowling that included terms related to workload. Population characteristics, variables relating to demand and their relationship to standardised definitions of physical activity were extracted from all included studies. Results Bowling workload is typically quantified through measures of frequency, duration, or indirect intensity, with few studies reporting on bowling volume. Conclusions When reported on, volume was often described using imprecise or insufficient measures of intensity. There is a need to develop more appropriate measures of intensity during bowling and improve the quality of evidence to inform on bowling programme management practices.